MRI findings in pregnancy related neurological complications - Khan, Laila; Rukhsana Aziz; Nishtar, Tahira (Journal of the Pakistan Medical Association, 2022)
Objectives: To describe the various neurological complications that occur in pregnancy and puerperium using magnetic resonance imaging as the diagnostic tool. Method: The prospective study was conducted at the Radiology Department of Lady Reading Hospital, Peshawar, Pakistan, from June 2018 to June 2019, and comprised pregnant and puerperium patients presenting with neurological symptoms who were referred for magnetic resonance imaging. Clinical records of the patients were reviewed for risk factors and neurological symptomatology. Imaging was done using a 1.5Tesla machine. Departmental routine imaging protocols for magnetic resonance imaging brain and magnetic resonance venography were used. Data was analysed using SPSS 23. Results: There were 60 pregnant women with a mean age of 25.85±5.1 years (range: 17-40 years). Magnetic resonance imaging showed posterior reversible encephalopathy syndrome in 20(33.3%) patients and haemorrhagic infarct in 18(30%), while 9(15%) were found to be normal. Magnetic resonance venography exhibited dural sinus thrombosis in 19(31.7%) patients. Conclusion: Magnetic resonance imaging was found to play a vital role in early diagnosis of pregnancy-related neurological complications. Key Words: MRI, Neurological complications, MRV, PRES, DST.